Knowledge, Attitude, and Associated Factors towards Nonpharmacological Pain Management among Nurses Working at Amhara Region Comprehensive Specialized Hospitals, Ethiopia - Esayas Alemshet Tekletsadik; Abebaw Alemayehu Desta; Belayneh Shetie Workneh (Critical Care Research and Practice)
Background. Nonpharmacological pain management refers to providing pain management intervention that does not involve the use of drugs. Effective management of a patient’s pain is a vital nursing activity, and it needs a nurse’s adequate pain-related knowledge and a favorable attitude. Globally, many studies stated that the lack of knowledge and unfavorable attitude of nurses towards nonpharmacological pain management was the prevailing persistent challenge. Objective. To assess knowledge, attitude, and associated factors towards nonpharmacological pain management among nurses working in Amhara region Comprehensive Specialized Hospitals, Ethiopia, 2021. Method. An institutional-based cross-sectional study was conducted from April to May 30, 2021. A total of 845 nurses were selected using a simple random sampling technique. Data were collected by using a pretested self-administered structured questionnaire. Then, data were checked, coded, and entered into Epi Info version 7.0 and exported to SPSS version 25.0 software for analysis. Results. A total of 775 nurses participated in this study, with a response rate of 91.8%. Of the total participants, 54.2% (95% CI: 50.6–57.9) and 49.8% (95% CI: 46.1–53.2) of nurses had adequate knowledge and a favorable attitude, respectively. The study revealed that educational status (AOR = 3.51 (95% CI: 1.37, 8.99)), years of experience (AOR = 5.59 (95% CI: 2.86, 10.94)), working unit (AOR = 5.61 (95% CI: 2.25, 13.96)), nurse-to-patient ratio (AOR = 2.33 (95% CI: 1.44, 3.78)), and working hours (AOR = 2.15 (95% CI: 1.27, 3.62)) were significantly associated. This finding also revealed that monthly income (AOR = 4.38 (95% CI: 1.64, 11.69)), nurse-to-patient ratio (AOR = 1.89 (95% CI: 1.19, 3.01)), and nurses’ adequate knowledge (AOR = 4.26 (95% CI: 2.91, 6.24)) were significantly associated with the attitude of nurses. Conclusion and Recommendations. More than half and nearly half of the nurses had adequate knowledge and a favorable attitude towards nonpharmacological pain management, respectively. Educational qualification, years of experience, working unit, nurse-to-patient ratio, and prolonged working hours per day were significantly associated with nurse’s adequate knowledge. Monthly income, nurse-to-patient ratio, and nurse’s knowledge were significantly associated with the attitudes of nurses. It is better to give attention to reviewing the nursing curriculum, achieving a standardized nurse-to-patient ratio, recruiting additional nurses, training, and upgrading nurses with continuing education.